PENGGUNAAN METODE LATTICE DALAM MENGATASI RENDAHNYA KEMAMPUAN BERHITUNG OPERASI PERKALIAN - Nur Khulaifatur Rosidah Solikin; Dyah Ayu Sulistyaning Cipta; Asri Putri Anugraini (Universitas Insan Budi Utomo, 2019)
One of the problems often faced by students is the low ability to calculate multiplication operations. One of the causes of this condition is still a lack of understanding of the two-digit multiplication concept and the procedure for working on it. In line with this, the existence of this study is expected to overcome the low ability to calculate multiplication operations of students by applying the lattice method. The aim of this study is describe of using the lattice method in overcoming the low ability to calculate multiplication operations. This research is a qualitative study. The stages in this study are divided into several treatments, where each treatment students get treatment from the introduction of the lattice method to use the advanced lattice method. The results of this study show that students are very interested in the new methods they know. They were able to complete independently the multiplication operation after going through four treatments that had been given. At the end of the treatment the average student achieved was 84.30 with a percentage of completeness reaching 96.56% and his numeracy ability increased by 0.81 (high category).